The mechanical control of nervous system development - Franze, Kristian (Development, 2013)
The development of the nervous system has so far, to a large extent, been considered in the context of biochemistry, molecular biology and genetics. However, there is growing evidence that many biological systems also integrate mechanical information when making decisions during differentiation, growth, proliferation, migration and general function. Based on recent findings, I hypothesize that several steps during nervous system development, including neural progenitor cell differentiation, neuronal migration, axon extension and the folding of the brain, rely on or are even driven by mechanical cues and forces. © 2013. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Brain folding; Force; Mechanics; Mechanosensitivity; Mechanotaxis; Mechanotransduction; Stiffness; Tension